Pengaruh Media Youtube dalam Pembelajaran PBL Terhadap Kemampuan Berpikir Kritis Siswa dan Pemecahan Masalah Siswa Kelas V - Amanda, Nadilla Resti; Risnawati, Risnawati; Vebrianto , Rian; Hamdani, M. Fikri (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the effect of YouTube media in PBL learning on critical thinking and problem solving skills of fifth grade students. The background of the researcher includes low problem-solving skills of students, lack of critical thinking skills of students towards social studies learning, and less than optimal use of learning media. This study used a pre-experimental design, specifically one-group pretest-posttest design. A total of 25 fifth grade students were used as research samples, which were carried out at SDN 184 Pekanbaru City. The data collection method used was a critical thinking and problem-solving skills test, while data analysis used descriptive and inductive analysis (normality test and hypothesis test). Based on the results of the study, the asymptotic significance value of the Wilcoxon test was 0.000 <0.05. Before and after therapy, students' critical thinking skills averaged 62.5 and 71.2, and their problem-solving abilities increased from 61.5 to 72.5. Therefore, it can be said that YouTube videos in PBL learning improve critical thinking and problem-solving abilities of fifth grade students